The Ability to Recognize Numbers Through the Singing Method in Group A Students - Silma Mubarokah (HADHANATUNA: Journal of Early Childhood Education, 2025)
This study is motivated by the challenges teachers face in introducing numbers to early childhood learners. The difficulty arises because numbers are abstract concepts, while young children predominantly think concretely. An effective and engaging method to facilitate number recognition is the singing method, which combines auditory, visual, and kinesthetic activities to make learning more enjoyable and memorable for children. In this study, the learning process involved several stages. First, the planning stage followed the 2013 Curriculum (K13), where the teacher determined appropriate teaching techniques and prepared relevant materials and teaching aids. During implementation, the teacher presented images and asked the children to identify the number of symbols depicted. The teacher then displayed the corresponding number shape, and the children were guided to complete the shape by tracing or marking the unfinished points. Finally, the evaluation stage aimed to enhance learning outcomes through interactive assessments, such as question-and-answer sessions and simple quizzes. The results indicate that the singing method effectively improves children’s number recognition, encourages active participation, and supports both cognitive and fine motor development. These findings suggest that integrating creative, multisensory methods in early childhood education can facilitate the understanding of abstract concepts like numbers in a more engaging and developmentally appropriate way.